Memory as representation/memory as experience: a study on Hatırla Sevgili through the narratives of leftists’ children in Turkey - Güzel, Zeynep. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study aims to analyze the experience(s) of leftists’ children through their narratives related to political past of Turkey and the television serial Hatırla Sevgili. To this end, in this thesis, within the context of 12 September 1980 military coup, the concept of individual memory is compared with the representation of the political past of Turkey in Hatırla Sevgili. The method of this study is based on narrative analysis and analysis of filmic representation. Secondly, this study examines the ways in which the leftists’ identity is characterized as innocent through the narratives of leftists themselves and by the narration of Hatırla Sevgili. Accordingly it is argued that this projection works as a dominant discourse, which prevents the other possibilities of articulations and interpretations on the same issue that would contribute to the analysis of the past. Finally, this study aims to illustrate how the experience(s) of leftists’ children have the potential of subverting the dominant narratives on the political past of Turkey.
Keywords: Memory.; Representative government and representation